(untitled) (JONAH : Journal of Nursing and Homecare, 2025)
Head nurses have the potential and a key role in fostering self-awareness and safety behaviors among nurses. However, the application of ergonomic principles in hospital settings, especially among nurses in intensive care and emergency departments, has not yet received full attention. Information on how head nurses perceive and experience ergonomic hazard prevention in these units remains limited. This qualitative study aimed to explore the experiences and perceptions of head nurses regarding ergonomic hazard prevention in nursing care. Data were collected through a Focus Group Discussion (FGD) conducted at a hospital in Pekanbaru, Indonesia. Participants consisted of all head nurses working in intensive care units and emergency departments. The data were analyzed using Colaizzi’s phenomenological strategy. The study revealed two main themes: The contribution of head nurses’ managerial functions in the prevention of ergonomic hazards, and the use of technology to support ergonomic hazard prevention among clinical nurses. All participants shared similar perceptions of the importance of ergonomic hazard prevention. The findings provide valuable insights that should be considered to improve ergonomic safety efforts in hospitals. Recommendations include the need for direction, motivation, and continuous education from head nurses, supported by technology such as smartphones equipped with educational content and reminder features.